Pemetaan Stakeholder Dalam Peningkatan Kesejahteraan Masyarakat Nelayan Di Pulau Pasaran Kelurahan Kota Karang, Kota Bandar Lampung - Dewi, Niken Puspita; Rochana, Erna; Damai, Abdullah Aman; Hartoyo, Hartoyo; Riantini, Maya; Febryano, Indra Gumay; Tresiana, Novita (Universitas Bangka Belitung, 2024)
The purpose of this study was to map the stakeholders involved in efforts to improve the welfare of fishing communities on Pasaran Island, Kota Karang Village, Bandar Lampung City. The data analysis method was carried out descriptively to map the stakeholders involved based on their interests and influence. The results showed that the players were the Lampung Provincial Government, Bandar Lampung City Government, Bandar Lampung City Fisheries Service, because these stakeholders have a very strong interest and influence. Stakeholders who act as context setters are the Ministry of Marine Affairs and Fisheries, Legislative Members, community leaders, NGOs, Goods and Services Providers, Police and TNI, Universities, because these stakeholders have great influence but low importance. The role of stakeholders with the subject category is small fishermen, namely labor fishermen and fish processing laborers, large fishermen and middlemen. Fishermen are stakeholders who have a high interest, but do not have a strong influence. Stakeholders in the crowd category are the Head of East Teluk Betung Sub-District, Head of Kota Karang Village, Neighborhood and RT officials in Kota Karang Village, because stakeholders, so that the expectations of the government for the provision of the program can be realized and the welfare of the fishing community will increase. In addition, community empowerment can also be carried out through developing the capacities of small fishermen and supporting information in the use of more developed fishing gear by conducting entrepreneurial training, developing skills and expertise for fishermen on Pasaran Island,